2022
DOI: 10.3389/fphar.2022.961347
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of tislelizumab versus chemotherapy as second-line treatment for advanced or metastatic esophageal squamous cell carcinoma in China

Abstract: Background and purpose: The latest RATIONALE-302 trial (NCT03430843) showed that tislelizumab therapy significantly improved overall survival benefits for patients with advanced or metastatic esophageal squamous cell carcinoma (ESCC) compared with traditional chemotherapy. This study aimed to compare the cost-effectiveness of tislelizumab versus chemotherapy as a second-line treatment for advanced or metastatic ESCC in China.Methods: A partitioned survival model was developed to predict patients’ lifetime qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 24 , 54 , 55 These studies found that camrelizumab was cost-effective in China. Shi et al 23 performed an economic evaluation of tislelizumab in second-line treatment for advanced OSCC from the Chinese healthcare payers’ perspective and estimated an ICER of $11,073.85 per QALY gained. These findings were consistent with our study, although the input parameters in these studies were slightly different from ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 54 , 55 These studies found that camrelizumab was cost-effective in China. Shi et al 23 performed an economic evaluation of tislelizumab in second-line treatment for advanced OSCC from the Chinese healthcare payers’ perspective and estimated an ICER of $11,073.85 per QALY gained. These findings were consistent with our study, although the input parameters in these studies were slightly different from ours.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 There is a scarcity of comprehensive economic assessments related to second-line treatment options, which are currently confined solely to comparisons between immunotherapy and chemotherapy. 23 25 Consequently, conducting pertinent cost-effectiveness analyses is imperative to properly address the dilemmas of policy formulation and clinical practice. 26 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous studies are targeted on the economic evaluations of immunotherapies for advanced ESCC patients and warrant discussion. At the current price and WTP threshold, domestic PD-1 inhibitors, such as camrelizumab, sintilimab, tislelizumab and toripalimab, were cost-effective options as first- or second-line treatment for patients with advanced ESCC in China ( 18 , 29 , 38 40 ). The dynamic adjustment mechanism of the national medical insurance catalog has played a predominant role in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of ESCC-related utility studies, the utility value parameters for this study were derived from a clinical study of adenocarcinoma of the stomach or gastroesophageal junction, which may have in uenced the results. However, the utility values from this study have been cited in several published ESCC-related economic evaluations [9,19,22,28,32,33] . Second, since the PFS curves of tislelizumab before and after MAIC adjustment relative to the chemotherapy group and the PFS curves of camrelizumab relative to the chemotherapy group did not meet the PH assumption, the HR values of both relative to the chemotherapy group were not used for the calculation of this study, but were extrapolated by tting the parameters to their respective IPDs, which may have biased the results to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the choice of model type and the perspective of the studies did not affect the results of the cost-effectiveness of camrelizumab versus the chemotherapy group. Shi et al used a PSM to compare the costeffectiveness of tislelizumab versus chemotherapy as a second-line treatment for advanced or metastatic ESCC in China and found that tislelizumab therapy was highly cost-effective compared with chemotherapy therapy [31] . It implied that tislelizumab could be a promising strategy for treating ESCC patients in the setting of China.…”
Section: Discussionmentioning
confidence: 99%